ON POSSIBILITIES OF VITAL MULTIPHOTON IMAGING OF IMMUNE REACTIONS IN THE STUDY OF INFLAMMATION PROCESSES (Experimental biology, 2026)
Inflammation is a universal, genetically programmed complex of reactions to damage of different nature aimed at elimination or limitation of the damage centre and pathogenic agents that caused it. Inflammatory reaction is one of the key mechanisms of innate immunity, the biological meaning of which is not only protection of the organism from pathogens, but also maintenance and restoration of damaged tissues. A thorough understanding of the mechanisms of inflammation is extremely important, as more than 70% of known human diseases are associated with the inflammatory process, including autoimmune, neurodegenerative, cardiovascular diseases, diabetes and cancer. Modern science and medicine have a large arsenal of methods and tools that allow for a multifaceted assessment of the state of the organism in inflammatory processes. Every year the use of non-invasive methods of research of different processes in the organism in real time becomes more accessible and acceptable for understanding cellular processes in dynamics. Vital microscopy is one of the modern tools applicable to the observation of immune cell dynamics. This literature review is devoted to the role of multiphoton microscopy in the study of mechanisms involved in the formation of immune response. Multiphoton microscopy makes it possible to study living tissues, as it has a high penetration depth and minimal phototoxicity. The use of this method allows to observe the course of cellular processes, such as cell migration, cell interaction, as well as to conduct studies of biological systems and cells in neurobiology, cardiology and other spheres.
Keywords: vital imaging, multiphoton microscopy, inflammatory process, immune cells, innate immunity